Lived experience of health care providers about preconception care for diabetic women - Nafiseh Sadat Nekuei; Sharareh Davazdah Emami (Iran University of Medical Sciences, 2010)
Background and Aim: Today, there is a lot of knowledge about care of diabetic pregnant women. Optimal care, before and during pregnancy is a suitable method to minimize the complications of diseases. Heath care providers are the important agents to deliver preconception care. The aim of this study was to understand lived experience of health care providers about preconception care for diabetic women.   Material and Method: This was a qualitative study with phenomenological approach in which 15 health care providers working in public and private centers in Isfahan, were selected by purposive sampling and in-depthly interviewed. Data analyzed was done by 7-stages Colaizzi's phenomenological method.   Results : According to experiences of health care providers, perfocmance and characteristics of health care system is important for high quality preconception care of diabetic women. Also, the results showed that knowledge of health care personnel about preconception care of diabetic women were not suitable. Findings (according to the experiences of participants) were classified into 3 main concepts: 1) Knowledge and attitude of personnel, 2) education of personnel, and, 3) health care system.   Conclusion: Continuous education for personnel and creating a suitable system to deliver preconception care for diabetic women is necessary.